2021
DOI: 10.1155/2021/2355258
|View full text |Cite
|
Sign up to set email alerts
|

Couple Stress Hybrid Nanofluid Flow through a Converging-Diverging Channel

Abstract: This research work is aimed at scrutinizing the mathematical model for the hybrid nanofluid flow in a converging and diverging channel. Titanium dioxide and silver are considered solid nanoparticles while blood is considered as a base solvent. The couple stress fluid model is essentially used to describe the blood flow. The radiation terminology is also included in the energy equation for the sustainability of drug delivery. The aim is to link the recent study with the applications of drug delivery. It is well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Priyadharshini et al [8] investigated the unsteady fow of collapsible tubes under transverse magnetohydrodynamic fuid. Ullah et al [9] conducted a numerical study on a magnetized 2D hybrid nanofuid (GO + ZnO + blood) fow through a porous capillary.…”
Section: Introductionmentioning
confidence: 99%
“…Priyadharshini et al [8] investigated the unsteady fow of collapsible tubes under transverse magnetohydrodynamic fuid. Ullah et al [9] conducted a numerical study on a magnetized 2D hybrid nanofuid (GO + ZnO + blood) fow through a porous capillary.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of heat transport in water/Cu and water/Ag between converging/diverging channel by implementing Least Square Method and thermal radiation, magnetic field effects in the presence of stretching/shrinking effects of the walls reported in Usman et al, 9 Dogonchi and Ganji, 10 respectively. Latest significant investigation regarding heat transport between converging/diverging channel (Akinshilo et al 11 ) under varying physical constraints like porous media effects, internal heat generation/absorption, the dynamics of blood suspended by nanoparticles 12 inside the channel with flexible walls, analytical treatment of heat transfer model through ADM, 13 and different nanofluids prepared by variety of nanoparticles and host solvent with different characteristics are examined by Ullah et al 14 and Kumar et al, 15 respectively. The researchers concluded that the hybrid nanoliquids have unique heat transport mechanism and very useful for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…Adnan et al [20] investigated the flow of Cu-water and Cu-kerosene oil through two Riga plates, taking into account surface convection and radiation effects. Zaka Ullah et al [21] studied the flow of a hybrid nanofluid in a diverging and a converging channel. The effects of ramped temperature, ramped concentration, chemical reaction, heat production, and magnetic force on Casson nanofluid flow via a conduit were studied by Sadiq et al [22].…”
Section: Introductionmentioning
confidence: 99%